2016
DOI: 10.3951/sobim.40.2_103
|View full text |Cite
|
Sign up to set email alerts
|

Dorsiflexion movement of the wrist by magnetic stimulation

Abstract: Magnetic pules stimulation was carried out for the peripheral nerve of the forearm of five healthy adults by using the magnetic stimulation device. Dorsiflexion movement of the wrist was measured using a digital goniometer under the following stimulus conditions. Magnetic field strength : 3 stage. Stimulation frequency 10 Hz to 50 Hz. Stimulation time : 0.5 to 2 sec. According to the stimulation conditions, wide range in bending angle of the wrist over 100 degree was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Various stimulus intensity has been used in NMES (Table ). We stimulated at a rate of 30 Hz for 2 sec, because greater movements were obtained at 30 Hz than 10 or 20 Hz in a previous study and 2 sec is the maximum on time in our system. However, the optimum intensity of magnetic stimulation should be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Various stimulus intensity has been used in NMES (Table ). We stimulated at a rate of 30 Hz for 2 sec, because greater movements were obtained at 30 Hz than 10 or 20 Hz in a previous study and 2 sec is the maximum on time in our system. However, the optimum intensity of magnetic stimulation should be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has confirmed the linear relationship between stimulus intensity and pulsed magnetic field intensity adjacent to the coil, what stimulus frequency can be adjusted in 2.5 Hz increments to any value within the range of 10–50 Hz. 20 – 22
Figure 1 Stimulus instruments.
…”
Section: Methodsmentioning
confidence: 99%
“…For both devices, the stimulus frequency was set at 30 Hz. 20 , 24 The stimuli were administered a total of 4 times at each intensity for a duration of 2 s each, with intervening 8 s breaks. Although the nature of the devices did not permit the use of an identical pulse width, the pulse widths were set as close to equivalent as possible, 350 µs for rPMS and 300 µs for TES.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, increased intensity of exogenous electrical stimulation can increase pain, and long-time application of electrical stimulation may become unpleasant or difficult 7 , 8 ) . Repetitive peripheral magnetic stimulation (rPMS) is less painful, increasing its clinical applications 9 ) . rPMS acts on intramuscular motor axons, which evoke muscle contraction 10 ) .…”
Section: Introductionmentioning
confidence: 99%